2010
DOI: 10.1038/ejhg.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of potential novel Graves' disease susceptibility loci, identified in the UK WTCCC genome-wide nonsynonymous SNP study

Abstract: A recent association scan using a genome-wide set of nonsynonymous coding single-nucleotide polymorphisms (nsSNPs) conducted in four diseases including Graves' disease (GD), identified nine novel possible regions of association with GD. We used a case-control approach in an attempt to replicate association of these nine regions in an independent collection of 1578 British GD patients and 1946 matched Caucasian controls. Although none of these loci showed evidence of association with GD in the independent data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Many of these studies rely on data from large case-specific studies such as the WTCCC [21], Farmingham Heart Study [22], or the International Cancer Genome Consortium (ICGC) [23]. Our study uses integrated data from all GWAS curated into the NIH GWAS Catalog.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies rely on data from large case-specific studies such as the WTCCC [21], Farmingham Heart Study [22], or the International Cancer Genome Consortium (ICGC) [23]. Our study uses integrated data from all GWAS curated into the NIH GWAS Catalog.…”
Section: Discussionmentioning
confidence: 99%
“…In the WTCCC study, although TSHR and FCRL3 loci were confirmed to be associated with GD, no additional locus was identified as a novel GD susceptibility locus. 14,25 Through the GWA and the subsequent replication studies, we identified 22 GD-associated SNPs within the MHC region. Among them, seven SNPs that were integrated into the multivariate logistic were successfully genotyped, 1119 GD cases versus 2718 controls, meta-analysis P-values), the replication study (34 SNPs, 432 GD cases versus 1157 controls, Cochrane-Armitage trend P-values) and the combined analysis of both studies (22 SNPs, 1551 GD cases versus 3875 controls, Cochrane-Armitage trend P-values), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although presently there is much less information linking KDMs to other therapeutic areas, there is suggestive genetic evidence that altered KDM activity may be relevant to a number of diseases. For instance, single nucleotide polymorphisms (SNPs) in KDM5A and KDM1A have been linked to the autoimmune diseases ankylosing spondylitis and Grave's disease respectively (Newby et al, 2010;Pointon et al, 2011). KDM6B has also been implicated in an autoimmune disease based on its overexpression in antineutrophil cytoplasmic autoantibody-associated vasculitis (Ciavatta et al, 2010).…”
Section: Lysine Demethylasesmentioning
confidence: 99%